The Concepts of Planning in Architecture and Environtment to Mitigate Tsunami Disaster Case Study: Semawang Beach, Denpasar, Bali - I Gede Surya Darmawan; I Wayan Wirya Sastrawan; Putu Hartawan (Architectural Research Journal, 2023)
Bali won the title of â€œWorld's Favorite Tourist Destination Destinationâ€ at the 2020 PVK Award. This title is inseparable from the many natural and cultural tourist objects that attract local and foreign tourists to visit Bali, one of which is Semawang Beach, Denpasar. The wide, white and shallow coastal area, calm sea conditions, a favorite place to enjoy the sunrise, the many gazebos and tourism accommodations, the location near Ngurah Rai International Airport is the main attraction for tourists. However, according to information from the Head of the National BMKG Prof. Dwikorita Karnawati said that the southern region of East Java and Bali, including Semawang Beach, has the threat of an earthquake accompanied by a tsunami in the future which we cannot predict exactly when it will occur. Based on this, it can be concluded that what is the solution, especially from the engineering side, especially architecture, which creates beaches that are safe for tourists to visit in the form of permeable architectural and environmental models that support tsunami disaster mitigation. Specifically for the first year, the existing model will be evaluated first so that it is hoped that in the second year a permeable design model will be produced. This study uses a descriptive qualitative approach using observation data, surveys, and documents. The research instruments were coastal base maps, total station tools, laser meters, stationery, autocad and 3d sketchup software, cameras and computers. The research which is planned for 9 months in the first year is expected to produce findings of evaluation of existing permeable architectural and environmental models in supporting tsunami disaster mitigation in the Semawang Beach area, Denpasar in terms of evacuation rescue routes, protective areas, safe zones, open spaces, facilities general disaster response, and determinants of disaster response in spatial planning and buildings.